Policy relevant heterogeneity in the value of statistical life: new evidence from panel data quantile regressions - Thomas J. Kniesner; William Kip Viscusi; James Patrick Ziliak (Institute for the Study of Labor (IZA), 2009)
We examine differences in the value of statistical life (VSL) across potential wage levels in panel data using quantile regressions with intercept heterogeneity. Latent heterogeneity is econometrically important and affects the estimated VSL. Our findings indicate that a reasonable average cost per expected life saved cut-off for health and safety regulations is 7 million to 8 million per life saved, but the VSL varies considerably across the labor force. Our results reconcile the previous discrepancies between hedonic VSL estimates and the values implied by theories linked to the coefficient of relative risk aversion. Because the VSL varies elastically with income, regulatory agencies should regularly update the VSL used in benefit assessments, increasing the VSL proportionally with changes in income over time.
urn:nbn:de:101:1-200911041024
Keywords: C23; I10; J17; J28; K00; 330; Value of statistical life; VSL; quantile regression; panel data; fixed effects; PSID; fatality risk; CFOI; Wert des Lebens; Menschen; Bewertung; Statistische Methode; Regression; Panel; USA